Gender gaps in political participation in Asia - Liu, Shan-Jan Sarah (International Political Science Review)
Recent scholarship shows that the gender gap in political activity has diminished, particularly in Western societies. Still unknown is how gender matters for political participation in Asia. Using the 2010 Asian Barometer Survey, this article analyzes the gender gap in multiple forms of political participation in 13 countries. It also investigates how individual-level characteristics mediate the differences in men$1 (Bs and women$1 (Bs political participation. The article shows that Asian men and women overwhelmingly vote at an equal rate in elections, but gender gaps persist in other types of political action. This study shows that gender remains the strongest predictor of political participation and suggests that Asian women remain marginalized in the political arena. The results have important implications for how to progress gender equality in the region.- Reproduced s
Keywords: Political participation, Gender gap, Asia, Public opinion, Gender equality